Combining preclinical tools and models to unravel tumor complexity: Jump into the next dimension - Miserocchi, Giacomo; Bocchini, Martine; Cortesi, Michela; Arienti, Chiara; De Vita, Alessandro; Liverani, Chiara; Mercatali, Laura; Bravaccini, Sara; Ulivi, Paola; Zanoni, Michele (Frontiers in Immunology, 2023)
Tumors are complex and heterogeneous diseases characterized by an intricate milieu and dynamically in connection with surrounding and distant tissues. In the last decades, great efforts have been made to develop novel preclinical models able to recapitulate the original features of tumors. However, the development of an in vitro functional and realistic tumor organ is still utopic and represents one of the major challenges to reproduce the architecture of the tumor ecosystem. A strategy to decrypt the whole picture and predict its behavior could be started from the validation of simplified biomimetic systems and then proceed with their integration. Variables such as the cellular and acellular composition of tumor microenvironment (TME) and its spatio-temporal distribution have to be considered in order to respect the dynamic evolution of the oncologic disease. In this perspective, we aim to explore the currently available strategies to improve and integrate in vitro and in vivo models, such as three-dimensional (3D) cultures, organoids, and zebrafish, in order to better understand the disease biology and improve the therapeutic approaches.